Preparation method of strong base and ammonia gas co-activation biomass-based activated carbon electrode material - LI MIN; GUO NANNAN; YANG RU (2018)
The invention relates to the field of preparation of electrode materials, in particular to a preparation method of a dual-activation biomass-based activated carbon electrode material. The preparationmethod comprises the steps of: pretreatment process of a biomass material; impregnation of a precursor and an activator solution; activation in an ammonia atmosphere, wherein the activation temperature is 600-900 DEG C and preferably 700-800 DEG C, and an ammonia gas flow is 0-300 ml/min and preferably 200 ml/min; washing, drying and grinding, so as to obtain an activated carbon material for supercapacitor electrodes; and conduction of electrical performance tests in different electrolyte systems. The product prepared by adopting the preparation method shows high energy density and long cyclelife in supercapacitors. 本发明涉及电极材料的制备领域，具体为双活化法生物质基活性炭电极材料的制备。该方法包括如下步骤：生物质材料的预处理过程；前驱体和活化剂溶液浸渍；氨气气氛下活化；其中活化温度为600-900℃，优选700-800℃，氨气流量为0-300ml/min；优选200 ml/min；洗涤、烘干、研磨，获得超级电容器电极用活性炭材料；并在不同电解液体系下进行了电性能测试。本发明制备出的产品在超级电容器中表现出高的